The Role of the Judiciary in Protecting the Financial Rights of Contractors with the Administration: An Application of the Theory of Force Majeure (Comprehensive Journal of Science, 2026)
This study aims to clarify and highlight the role of administrative courts in protecting the financial rights of contractors with the administration when unforeseen circumstances affect contract execution. It also analyzes how the judiciary intervenes to restore the financial balance of the contract when it is disrupted by these circumstances, and emphasizes the guarantees afforded to contractors against unexpected losses. The study concludes that the judiciary is crucial as it represents the primary safeguard for contractors against any administrative practices that may infringe upon their financial rights. Furthermore, it oversees administrative actions to ensure compliance with applicable laws and regulations.
Keywords: Judiciary - Financial Rights - Contract - Administration - Theory of Unforeseen Circumstances